Exploring the relevance of the type of horizontal separator to optimize the extraction efficacy for the Arbequina variety - Boudebouz, Abdelaziz; Hermoso, Juan-F; Martí, Esteve; Ninot, Antonia; Boqué, Ricard; Mestres, Montserrat; Aceña, Laura; Veneziani, Gianluca; Selvaggini, Roberto; Servili, Maurizio; Romero, Agustí (Frontiers in Plant Science, 2024)
The productivity of virgin olive oil depends not only on agronomic factors but also on the technological factors of the extraction process. The ‘Arbequina’ variety has extractability problems, which is a challenge for master millers anywhere. This work aims to evaluate the behavior of different decanters and seeks to modulate the effect of some processing parameters and their interactions with oil extraction efficiency in the case of ‘Arbequina.’ Fruit characteristics, processing parameters, and extractability were collected over 10 years from 38 decanters that belong to five different brands. The results have shown that fruit moisture is the most relevant factor for oil extractability, especially over 52%. Furthermore, extractability is positively correlated with malaxing temperature, addition of water, and total fat content in the fruit. However, the results show that before applying a regulation, the type of decanter must be considered. The model used in this study has allowed us to optimize the regulations for each type of decanter to reduce oil losses within the pomace, achieving an extraction efficiency within the range of 78%–91.5%. In fact, the best extraction efficiency results (91.5%) were obtained by processing at temperatures >26°C and water injection of 5%.